Therapeutic use of growth factors in the musculoskeletal system in sports-related injuries - Bachl, N.; Derman, W.; Engebretsen, L.; Goldspink, G.; Kinzlbauer, M.; Tschan, H.; Volpi, P.; Venter, D.; Wessner, B. (The Journal of Sports Medicine and Physical Fitness, 2009)
Growth factors (GFs) act as signalling agents for cells and become a more and more popular mean to influence the human body and its tissues. This review gives an overview of the current possibilities to use such agents in the field of sports related injuries and thus providing the athlete with a whole new potential to minimize recovery time. GFs and its application have been studied intensively for a long time starting with animal studies. For some of this GFs this research has been brought onto the next level to clinical phase trials. Agents such as insulin like growth factor 1 (IGF-1), mechano growth factor (MGF), basic fibroblast growth factor (B-FGF), platelet derived growth factor (PDGF), vascular endothelial growth factor (VEGF), transforming growth factor b (TGF-b), bone morphogenetic protein (BMP) and leukemia inhibitory factor (LIF) are being discussed in this review. These GFs not only have the potential to be used to cure injuries but also are being in the centre of interest for doping abusers and are a powerful yet not fully understood technique to gain performance.